Development Of Socialisation Materials On The Negative Impact Of Smartphones On Early Childhood: Guidance For Teachers Who Are Members Of IGRA - Muhtarom; Sartika, Indah Dwi (Raudhatul Athfal: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Rapid technological advances have brought significant changes to people's lifestyles and social aspects. In today's digital era, the use of technology is no longer limited to certain age groups—even children are now familiar with devices such as smartphones. Although smartphones offer many conveniences, their use also has negative impacts, especially for early childhood. This community service activity aims to assist teachers in developing educational materials on the adverse effects of smartphone use on early childhood. This community service activity used a participatory action research (PAR) approach. The subjects of this activity were Raudhatul Athfal (RA) teachers who are members of IGRA Palembang City. Data collection techniques used in this activity included interviews, observation, and documentation. Data analysis techniques used in this activity included qualitative data analysis and quantitative data analysis. The results of the activity showed that most teachers already had a basic understanding of the negative impacts of smartphones but did not yet have structured socialisation materials. Through this assistance process, the teachers successfully developed interesting and informative educational materials that can be used to provide better understanding to parents and children. It is hoped that this activity can make a positive contribution in minimising the negative impacts of smartphone use and support the optimal growth and development of early childhood.